(untitled) (Journal of Social Economics Research, 2025)
This paper discusses the effects of trustworthiness, business loyalty (BL), perseverance, and relationship quality (RQ) on environmental volatility (ET). Assessment of a Likert-scale survey questionnaire was conducted to analyze the average value for each item, indicator, and variable in a descriptive manner. Data collection was done via a manual sample survey. Analyzed data using Structural Equation Modeling (SEM) on Smart PLS (partial least squares) 3.0. The study’s findings indicate that while it has both a short- and long-term impact on loyalist business operations, it has a greater impact on long-term business operations with high-quality connections and short-term business operations with a fluctuating environment. The research findings demonstrate a direct correlation between trustworthiness and the quality of business-to-business and loyalty relationships. This is a result of the sugarcane farmer’s relatively low level of trustworthiness when it comes to consistently reporting the results to the sugar plant; this is caused by the relatively low quality of the partnership.